Optimization of Profit Sharing Financing in MSME Development in Medan Sharia People's Financing Bank (BPRS) - Nina Andriany Nasution; Vina Arnita (Proceeding of The International Conference on Economics and Business, 2023)
Develop MSMEs more quickly through capital facility policies in optimizing financing and obtaining profits with the profit sharing method at the Medan Sharia People's Financing Bank (BPRS). Based on this phenomenon, this research is intended to look at Financing Optimization, Mudharabah Financing and Profit Sharing at the Medan Sharia People's Financing Bank (BPRS). This type of research with a quantitative descriptive approach with secondary data. The data analysis technique used in this study is Multiple Linear Regression Analysis. The results of this study indicate that Optimization of Financing has a positive and significant partial effect on MSME Development, this is done if the objective of optimizing financing is related to profits. Mudharabah financing has a partially positive and significant effect on the development of MSMEs, this occurs because the level of financing can be seen from the increase in sales turnover. Profit Sharing has a positive and significant partial effect on MSME development, because the net profit obtained from MSME activities is shared by looking at the increase in MSME equity (net activation). The most common Micro, Small and Medium Enterprises (MSMEs) faced by companies are Asset development in MSMEs has been defined based on net worth and annual sales results which show that the Micro, Small and Medium Enterprises (MSMEs) segment in Indonesia has a strategically important role in economic development. Government regulations further regulate business development, partnerships, licensing, as well as coordination and control of Micro, Small and Medium Enterprises (MSMEs). Small, medium and micro businesses cannot repay loans to the financial sector, such as banks and non-banks (cooperatives), so there is a risk of default by the debtor (non-payment). On the other hand, liquidity in the financial sector was disrupted by a large increase in member withdrawals, but this was not offset by income from member loan repayments. This had a significant impact on members' distrust in the financial sector, which Financing Optimization, Mudharabah Financing and Profit Sharing have a positive and significant simultaneous effect on MSME Development. The regulation describes the standards for Micro, Small and Medium Enterprises (MSMEs) in Indonesia, namely: a. Micro Enterprises are productive businesses owned by individuals or individual business entities that meet the criteria for small businesses